2023
DOI: 10.1002/ppul.26333
|View full text |Cite
|
Sign up to set email alerts
|

Impulse oscillometry in preschool children with persistent asthma can predict spirometry at school age

Abstract: Background: Lung function in children with persistent asthma may be impaired during preschool and school ages. The aim of this study was to describe if some preschool impulse oscillometry (IOS) parameters are related to spirometry alterations on reaching school age.Methods: In 66 diagnosed with persistent asthma, an IOS was performed at entrance and followed-up to school age where a spirometry was done. Results:The mean age was 4.9 years at the first evaluation and 7.9 years at the second evaluation, and 59.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The Chilean study, 1 in line with the two Finnish studies, 2,3 confirmed that IOS at preschool age in asthmatics was able to identify those patients who later had reduced FVS. Our postbronchiolitis cohort study 4 showed similar results in nonasthmatics, who constituted the great majority, 87% to 88%, of the cases at 6.2 and 12.3 years follow‐up visits.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…The Chilean study, 1 in line with the two Finnish studies, 2,3 confirmed that IOS at preschool age in asthmatics was able to identify those patients who later had reduced FVS. Our postbronchiolitis cohort study 4 showed similar results in nonasthmatics, who constituted the great majority, 87% to 88%, of the cases at 6.2 and 12.3 years follow‐up visits.…”
mentioning
confidence: 63%
“…The appropriate LR+ limits are dependent on the pretest probability, which depends on the severity of cases. In the study of Grell et al 1 all children had persistent asthma. The authors do not report the associations between IOS and post‐BD FVS parameters, but LR+ values for pre‐BD parameters were so high, that probably, the conclusions would have been similar.…”
mentioning
confidence: 94%
See 3 more Smart Citations